An EBIC and SRP study on thermal donors in proton implanted p‐type magnetic Czochralski silicon. Issue 11 (8th August 2014) - Faccinelli, Martin; Kirnstoetter, Stefan; Schustereder, Werner; Laven, Johannes G.; Hadley, Peter; Pizzini, Sergio; Kissinger, Gudrun
Abstract The concentration of defects in silicon can be changed by ion implantations and thermal annealing steps. Some of the defects incorporated during these processes form complexes which can act as donors or acceptors and their concentration can even overcome the initial doping concentration of the material, and hence, cause an inversion of the doping type. One way to introduce defects and also to catalyse the formation of defect complexes is by proton implantation. For our project, a high resistivity p‐type magnetic Czochralski (m:Cz) grown silicon wafer was implanted with 4 MeV protons at an implantation dose of 2 ×1014 cm–2. The wafer was broken into pieces and these pieces were annealed at different temperatures resulting in different concentrations of defect complexes. The defects were investigated in the proton implanted region and in the substrate region beyond the penetration depth of the protons (where only the heat treatment caused a change in the defect concentrations). The local doping type and the relative change of the minority carrier diffusion length were measured using Electron Beam Induced Current (EBIC). Furthermore, resistivity profiles were measured using Spreading Resistance Profiling (SRP). The results show several changes of the doping type, the minority carrier diffusion length and the resistivity profile. In addition to donor complexes already reported in the literature, the formation of additional high temperature donor complexes has been observed. The data shows that the presence of hydrogen in silicon has a far higher influence on the changes of the electrical properties of the material at annealing temperatures between 400 °C and 510 °C than at higher annealing temperatures. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)